Reduced sCD36 following weight loss corresponds to improved insulin sensitivity, dyslipidemia and liver fat in obese children - Knøsgaard, L; Kazankov, K; Birkebæk, N H; Holland-Fischer, P; Lange, A; Solvig, J; Hørlyck, A; Kristensen, K; Rittig, S; Vilstrup, H; Grønbæk, H; Handberg, A (European journal of clinical nutrition, 2016)
Background/Objectives: Childhood obesity is a major health problem with serious long-term metabolic consequences. CD36 is important for the development of obesity-related complications among adults. We aimed to investigate circulating sCD36 during weight loss in childhood obesity and its associations with insulin resistance, dyslipidemia, hepatic fat accumulation and low-grade inflammation. Subjects/Methods: The impact of a 10-week weight loss camp for obese children ( N =113) on plasma sCD36 and further after a 12-month follow-up ( N =68) was investigated. Clinical and biochemical data were collected, and sCD36 was measured by an in-house assay. Liver fat was estimated by ultrasonography and insulin resistance by the homeostasis model assessment (HOMA-IR). Results: Along with marked weight loss, sCD36 was reduced by 21% ( P =0.0013) following lifestyle intervention, and individual sCD36 reductions were significantly associated with the corresponding decreases in HOMA-IR, triglycerides and total cholesterol. The largest sCD36 decrease occurred among children who reduced HOMA-IR and liver fat. After 12 months of follow-up, sCD36 was increased ( P =0.014) and the metabolic improvements were largely lost. Conclusions: Weight-loss-induced sCD36 reduction, coincident with improved insulin resistance, circulating lipids and hepatic fat accumulation, proposes that sCD36 may be an early marker of long-term health risk associated with obesity-related complications.